Greenhouse Berbasis IOT ( Internet Of Things ) Sistem Monitoring Dan Kontrol Lingkungan Tanaman Tomat - Hendra Wardana, Aliefian; Wahyu Febriyanto, Ridwan; Said Fathullah, Umar (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2025)
This research aims to develop Internet of Things (IoT)-based monitoring and control system in the greenhouse environment for tomato plants. This system utilizes NodeMCU microcontroller, ESP8266, soil temperature and humidity sensors, and Blynk application to monitor the greenhouse environment. ESP8266 microcontroller, soil temperature and humidity sensors, and Blynk application to monitor real-time data. data in real-time. Based on the measurements taken, the air temperature ranges from 22°C to 30°C during the day and 17°C to 19°C at night. at night. Soil moisture was recorded between 40% to 75%, where the system automatically activated actuators such as fans and automatically activates actuators such as fans and water pumps when conditions exceed or fall short of a predetermined threshold. These results show that the system is able to keep the temperature and humidity within the ideal range (24-26°C daytime, 16-18°C nighttime). (24-26°C daytime, 16-18°C nighttime for the flowering phase; and 21-27°C daytime, 15-20°C nighttime for the seedling phase), as well as humidity within the ideal range of night for the seedling phase), as well as ideal soil moisture between 60%-80%. The system This system has proven to be effective in reducing manual intervention and supporting optimal growth of tomato plants.